How Leadership and Job Satisfaction Influence OCB: The Mediating Role of Organizational Commitment ? - Wahyu, Anang Wahyu; Suhana , Suhana (Amkop Management Accounting Review (AMAR), 2025)
The purpose of this study is to identify potential factors that enhance teachers' Organizational Citizenship Behavior (OCB) in schools. Specifically, this research investigates the influence of transformational leadership and job satisfaction on organizational commitment and OCB, as well as analyzing the mediating role of organizational commitment in the relationship between transformational leadership and job satisfaction on OCB. The respondents of this research were 140 non-ASN Early Childhood Education teachers in Pekalongan City. Data collection used questionnaires as research instruments. Data analysis was conducted using SEM-PLS method and SmartPLS4.1 software. The results showed that Transformational Leadership does not influence OCB; Transformational Leadership does not influence Organizational Commitment; Job Satisfaction significantly influences OCB; Job Satisfaction significantly influences Organizational Commitment; Organizational Commitment significantly influences OCB; Organizational Commitment mediates the influence of Job Satisfaction on OCB, but not the influence of Transformational Leadership on OCB. The research has theoretical and managerial implications.